Therapeutic Potential of Natural Plants Against Non-Alcoholic Fatty Liver Disease: Targeting the Interplay Between Gut Microbiota and Bile Acids - Sun, QinMei; Xin, Xin; An, ZiMing; Hu, YiYang; Feng, Qin (Frontiers in Cellular and Infection Microbiology, 2022)
Non-alcoholic fatty liver disease (NAFLD) remains a common disease with a significant health and economic burden worldwide. The gut microbiota (GM) and bile acids (BAs), which play important roles in the gut-liver axis, have been confirmed to jointly participate in the development of NAFLD. GM not only regulate bile acids’ synthesis, transport, and reabsorption by regulating other metabolites (such as trimetlyl amine oxide, butyrate), but also regulate dehydrogenation, dehydroxylation and desulfurization of bile acids. Meanwhile, disordered bile acids influence the gut microbiota mainly through promoting the bacterial death and lowering the microbial diversity. Although weight loss and lifestyle changes are effective in the treatment of NAFLD, the acceptability and compliance of patients are poor. Recently, increasing natural plants and their active ingredients have been proved to alleviate NAFLD by modulating the joint action of gut microbiota and bile acids, and considered to be promising potential candidates. In this review, we discuss the efficacy of natural plants in treating NAFLD in the context of their regulation of the complex interplay between the gut microbiota and bile acids, the crosstalk of which has been shown to significantly promote the progression of NAFLD. Herein, we summarize the prior work on this topic and further suggest future research directions in the field.